2021
DOI: 10.1038/s41598-021-96227-5
|View full text |Cite
|
Sign up to set email alerts
|

High-content image-based analysis and proteomic profiling identifies Tau phosphorylation inhibitors in a human iPSC-derived glutamatergic neuronal model of tauopathy

Abstract: Mutations in MAPT (microtubule-associated protein tau) cause frontotemporal dementia (FTD). MAPT mutations are associated with abnormal tau phosphorylation levels and accumulation of misfolded tau protein that can propagate between neurons ultimately leading to cell death (tauopathy). Recently, a p.A152T tau variant was identified as a risk factor for FTD, Alzheimer's disease, and synucleinopathies. Here we used induced pluripotent stem cells (iPSC) from a patient carrying this p.A152T variant to create a robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Human stem cell-derived neurons provide the possibility of using human neurons for AD study. The ability to differentiate iNs via Ngn2 overexpression significantly benefits the study of AD [ 34 , 51 , 52 , 53 ]. In this study, iNs were used to determine the protective role of AR inhibition in neuronal death caused by β-amyloid-activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Human stem cell-derived neurons provide the possibility of using human neurons for AD study. The ability to differentiate iNs via Ngn2 overexpression significantly benefits the study of AD [ 34 , 51 , 52 , 53 ]. In this study, iNs were used to determine the protective role of AR inhibition in neuronal death caused by β-amyloid-activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Human induced pluripotent stem cell models have been increasingly utilized to study AD because brain-relevant cell types can be studied in vitro and used to profile molecules that may modify these disease phenotypes. Indeed, hiPSC-derived cells have been employed in several screens of small molecules hypothesized to impact AD processes, however, the majority of these experiments have been performed in neuronal cells and largely focused on the effects of compounds on Aβ and tau ( Brownjohn et al, 2017 ; Kondo et al, 2017 ; van der Kant et al, 2019 ; Cheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these disease phenotypes were reversable providing elegant platforms for high-throughput drug screening for compounds in pre-clinical settings to be able to potentially interfere at an early stage of the disease development process. In fact, human iPSC-derived drug screening platforms have been established ( Wang et al, 2017 ; Cheng et al, 2021 ) and large numbers of patient-derived neural cells can readily be derived, cultured and tested in such dynamic cellular assays in vitro , in contrast to alternative approaches involving genetic mouse models or postmortem brain material from patients. Such drug screening assays may also involve the co-culture of patient iPSC-derived neurons with patient iPSC-derived glial cells such as astrocytes to test glia- or even neuron-mediated non-cell autonomous mechanism of disease development in neurodegenerative diseases, such as FTLD-tau.…”
Section: Discussionmentioning
confidence: 99%
“…The same group later applied a high-content imaging assay on A152T and control cortical neurons to screen for kinases and small molecules to reduce tau and p-tau expression as well as their somatodendritic redistribution ( Cheng et al, 2021 ). This study revealed that the GSK-3 inhibitor CHIR-99021 and the kinase inhibitors enzastaurin and ruboxistaurin reduced p-tau in cell processes and cell body in A152T and control neurons and that the small molecule kinase inhibitors AT7519 and CGP-60474, as part of a collection of 44 kinase inhibitors, had similar effects in a screen on A152T neurons.…”
Section: Human Induced Pluripotent Stem Cell Models Of Frontotemporal Lobar Degeneration With Tau Pathologymentioning
confidence: 99%
See 1 more Smart Citation